Socialisation of the Blue Economy Concept in the Development of Coastal Tourism Areas in Makassar City - Taufiqur Rachman; Juswan .; Daeng Paroka; Muhammad Zubair Muis Alie; Bulan Purnama; Ardi . (Faculty of Engineering UNHAS, 2024)
Indonesia is one of 193 countries committed to the sustainable development goals (SDGs). In this new paradigm of sustainable Indonesian development, the maritime sector is a priority for future development with the concept of blue economy, which is a sustainable ocean economy that produces economic and social benefits with the assurance of long-term environmental sustainability. The focus of the blue economy with this maritime economic strategy makes coastal communities the centre of blue economy growth. Makassar City has a coastal tourism area located in Tanjung Merdeka Village, Tamalate District Makassar, and is managed community-based by Non-Governmental Organizations (NGO) of Tanjung Merdeka. To maintain the sustainability process of coastal tourism area management, it is necessary to understand the concept of blue economy according to the maritime development strategy. Socialisation of the concept of blue economy in the development of coastal tourism areas in Makassar City has been carried out and achieved an increase in knowledge and understanding of participants by 50%. Understanding the concept of sustainable coastal and marine resource management, as well as how to participate in facing the challenges of environmental degradation and climate change, will complement the role of Tanjung Merdeka NGO as a tourism manager with the concept of blue economy. Assessment of the application of the concept of blue economy in coastal tourism areas has been carried out and fulfils the concept of blue economy according to Pauli's theory (2010).